TimeFun-InSAR Algorithm to Investigate Physical Changes at Bromo Volcano by Using ALOS/PALSAR Data Sets - Arliandy Pratama Arbad; Wataru Takeuchi; Yosuke Aoki (Department of Urban and Regional Planning, Diponegoro University, 2020)
Mt. Bromo is geographically located in eastern of Java Island at 112°57'30'' longitude and 7°56' latitude, with a large area of caldera 10 Km2. The land over the volcano is a perfect area for farming, one of the important factor affects the level of soil fertility is the most mineral rich soils. Volcanic activities at Mt. Bromo has been recorded in 1775 which characterized by small eruptions with cycles ranging from one to five years. Regarding this evidence, we tried to investigate the surface changes over the Mt. Bromo by using Time-Series InSAR with TimeFun algorithm. TimeFun is an extension of SBAS to allow incorporating various functions such as seasonal oscillations, polynomials, and step functions as generally it estimates DEM errors as well and allows missing observation. The maximum allowed baseline value is defined and used to constrain the interferogram pair by selecting manual after differential InSAR processing in single face working. The proposed analysis is based on 27 SAR data sets acquired by the ALOS/PALSAR sensors during the 2007–2017 time interval. The result shows us deformation occurred up to 10 cm at summit of Mt. Bromo during the eruption period. Time-series monitoring of surface deformation to infer volume changes, geometries and locations of sources of deformation involved in the future eruption